Long-term efficacy analysis of the randomised, phase II TRYPHAENA cardiac safety study: Evaluating pertuzumab and trastuzumab plus standard neoadjuvant anthracycline-containing and anthracycline-free chemotherapy regimens in patients with HER2-positive early breast cancer. (January 2018) - Schneeweiss, Andreas; Chia, Stephen; Hickish, Tamas; Harvey, Vernon; Eniu, Alexandru; Waldron-Lynch, Maeve; Eng-Wong, Jennifer; Kirk, Sarah; Cortés, Javier
Abstract: Background: We report long-term efficacy and cardiac safety outcomes in patients with HER2-positive early breast cancer treated with neoadjuvant pertuzumab plus trastuzumab with anthracycline-containing or anthracycline-free chemotherapy. Methods: Descriptive efficacy analyses were conducted in patients randomised to group A (cycles 1–6: trastuzumab [8 mg/kg loading dose and 6 mg/kg maintenance] plus pertuzumab [840 mg loading dose and 420 mg maintenance], plus 5-fluorouracil, epirubicin and cyclophosphamide [FEC] [cycles 1–3; 500 mg/m 2 5-fluorouracil/100 mg/m 2 epirubicin/600 mg/m 2 cyclophosphamide] then docetaxel [cycles 4–6; 75 mg/m 2, escalated to 100 mg/m 2 if well tolerated]), B (cycles 1–3: FEC, cycles 4–6: trastuzumab plus pertuzumab plus docetaxel as mentioned previously) or C (cycles 1–6: trastuzumab plus pertuzumab plus docetaxel [75 mg/m 2, without dose escalation], and carboplatin [AUC 6]), five years after randomisation of the last patient. This study is registered withClinicalTrials.gov, numberNCT00976989 . Results: Three-year Kaplan–Meier survival estimates for disease-free survival (DFS) were 87% (95% confidence interval: 79–95), 88% (80–96) and 90% (82–97) in groups A–C, respectively. Progression-free survival (PFS) rates were 89% (81–96), 89% (81–96) and 87% (80–95). DFS hazard ratio for total pathological complete response (tpCR) versus no tpCR was 0.27 (0.11–0.64). During post-treatment follow-up, 2/72 (2.8%), 3/75 (4.0%) and 4/76 (5.4%) patients in groups A–C had any-grade left ventricular systolic dysfunction; eight (11.1%), 12 (16.0%) and nine (11.8%) patients experienced left ventricular ejection fraction declines ≥10% from baseline to <50%. Conclusions: Long-term DFS and PFS were similar between groups. Patients who achieved tpCR had improved DFS. No new safety signals were identified. Highlights: Long-term survival outcomes were similar across treatment arms in the TRYPHAENA study. Total pathological complete response was associated with improved disease-free survival. No new cardiac safety signals were identified during long-term follow-up.